THE EFFICIENCY OF THE PROTECTION OF FUNDAMENTAL RIGHTS IN THE EUROPEAN UNION AFTER THE SO-CALLED LISBON REFORM. A LOOK AT SOME CRUCIAL ISSUES - Zbigniew, Witkowski; Katarzyna, Chrzczonowicz Witkowska; Piotr, Chrzczonowicz (Anales Universitatis Apulensis Series Jurisprudentia, 2013)
Abstract The paper focuses on some crucial issues concerning the protection of human rights in the European Union after the entry into force of the Treaty of Lisbon. This so-called Lisbon Reform - in the context of issues emphasized by the authors of the paper - has changed hitherto existing legal environment considerably. Enlargement and strengthening of the protection of fundamental rights within the legal system of the European Union is an unquestionable fact. In the paper, particular attention is paid to the entry into force of the Charter of Fundamental Rights of the European Union together with the Protocol No. 30 (so-called Polish – British Protocol), as well as to the analysis of the perspectives and conditions of the accession of the European Union to the European Convention for the Protection of Human Rights and Fundamental Freedoms of 1950. Such accession is nowadays one of the most important challenges, both for the European Union and the Council of Europe. Its significant result will be the necessity of creation – through the strict co-operation of these two organizations – of the coherent and effective system of the protection of human rights. Keywords: the protection of human rights, the European Union, The Charter of Fundamental Rights, The Lisbon Treaty, The Council of Europe.